A rare case of symphalangism of bilateral interphalangial joint of thumbs: a case report - Kumar, Anil (International Surgery Journal, 2020)
Symphalangism is rare congenital disorder characterised by ankylosis of interphalangeal joints of hands and feet. The fusion can involve the proximal or the distal joints; however, involvement of the proximal interphalangeal joints is more common. There may other associated skeletol and non-skeletol abnormalities. Here the author reports a 14 year old girl with symphalangism involving the interphalangeal joints of the thumbs of bilateral hand. She did not have any functional impairment and hence no medical or surgical intervention was performed. As involvement of thumbs is very rare condition, author would like to report it.